Vegetation analysis of medicinal plant in Dho-tarap area of upper Dholpo, Mid-western, Nepal - Rokaya, MB; Ghimire, SK (Botanica Orientalis: Journal of Plant Science, 2007)
Botanica Orientalis Vol.4(1) 2004. p.46-50